Molecular identification of diminazene aceturate resistant trypanosomes in tsetse flies from Yoko in the Centre region of Cameroon and its epidemiological implications. (May 2020) - Simo, Gustave; Magang, Eugenie Melaine Kemta; Mewamba, Estelle Mezajou; Farikou, Oumarou; Kamga, Rolin Mitterran Ndeffo; Tume, Christopher; Solano, Philippe; Ravel, Sophie
Abstract: African animal trypanosomiases are caused by trypanosomes cyclically or mechanically transmitted by tsetse and other biting flies. Although molecular tools have been developed to identify drug-resistant trypanosomes in mammals, little or no investigation on drug-resistance has been undertaken on trypanosomes harbored by tsetse flies. Moreover, no data on mechanical vectors of African trypanosomes is available in most endemic areas of Cameroon. This study was designed to update our knowledge on the cyclical and mechanical vectors of African trypanosomes, and using molecular tools to identify different trypanosome species as well as diminazene aceturate resistant trypanosomes in tsetse flies trapped at Yoko in the Centre region of Cameroon. For this study, traps were used to catch tsetse and mechanical vectors of African trypanosomes. The flies trapped were counted and identified by sex and species. DNA was extracted from tsetse and species-specific primers were used to identify different trypanosome species. PCR-RFLP was used to detect diminazene aceturate resistant strains of Trypanosoma congolense . In all, 454 flies comprising 168 (37%) Tabanus spp., 71 (15.6%) Stomoxys spp. and 215 (47.4%) tsetse fly ( i.e. 107 (49.8%) Glossina fusca congolensis, 71 (33%) Glossina fusca fusca and 37 (17.2%) Glossina palpalis palpalis ) were trapped. Trypanosome infections were identified in 12.6% (27/215) of tsetse flies: 13 in G. f. congolensis, 6 in G. p. palpalis and 5 in G. f. fusca . From 24 T. congolense positive samples, PCR-RFLP was successful on 37.5% of the samples. Four samples (16.2%) harbored T. congolense strains that were resistant to diminazene aceturate while the remaining samples had drug-sensitive strains. These results show for the first time the applicability of molecular tools for the identification of drug-resistant trypanosomes in tsetse. They revealed the existence of diminazene aceturate resistant strains of T. congolense in the tsetse-infested area of Yoko in the Centre region of Cameroon. Detection of drug-resistant trypanosomes in tsetse may enable scientists to map with accuracy specific areas where these parasites are transmitted. With such mapping, control strategies against African trypanosomiases could be improved by adapting control measures according to drug resistance distribution. Graphical abstract: Unlabelled Image